POTENSI FAMILI MYRTACEAE SEBAGAI ANTIHIPERURISEMIA : REVIEW - Jamilah, Putri Ayu Nurul; Riyanti, Soraya (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Hyperuricemia is a condition of uric acid levels that have increased beyond normal limits in the blood. The prevalence of gout in Indonesia has increased by 11.9% and generally the highest prevalence is at the age of ≥ 75 years at 54.8%. Based on information, gout sufferers in women are higher (8.46%) compared to men (6.13%). The utilization of medicinal plants has been widely practiced by the community in dealing with the problem of gout. This article discusses several plants of the Myrtaceae family that are widely used by the community as traditional medicine in dealing with uric acid problems or as antihyperuricemia. The literature search method was carried out online to get articles from national and international journals. The results of the literature search obtained several plants of the Myrtaceae family, namely Salam (Syzygium polyanthum Wight.), guava (Psidium guajava L.), jamblang (Syzygium cumini L.), cloves (Syzygium cumini L.), and clove (Syzygium cumini L.). ), cloves (Syzygium aromaticum), Kupa (Syzygium polycephalum), guava rose (Syzygium jambos L.), and red shoots (Syzygium myrtifolium Walp.) that have antihyperuricemia activity through In vivo and In vitro testing. This review article can provide information about the potential of the Myrtaceae family that has activity as antihyperuricemia.